THE EFFECT OF THE BIOFEEDBACK'S TECHNIC IN THE ATTENTION OF THE YOUTHFUL'S ATHLETES FROM (Fiep Bulletin - online, 2015)
Objective: Checking the tecnic's application of the biofeedback about the attention of the youthful's athletes from field's soccer, 20 fellows, male, 15 years old that belong from the same team, a daily training of 2 hours and middle weekly games. They are separated with uniformity: (G1) experimental group, (G2) control . It was utilized the Harris & Harris' test (1984). It was checked the visual selective attention from a duration short with a memory of work (AVMTT) and no memory of work(AVT.). Seven interventions about 10 minutes. They are perfomed though of a softaware named Mentalgames (Audiostrobe), that consisted in control about a stimulate in the computer, They are commanted though of the skyn galvanization reply(RGP). To the  analyse between dust and after the test, It was utilized the test from Wilconox . The results of the experimental group to the AVMT2 of 18,8+86s and  13,3+4,1s, to the AVMTT of 8,9+ 1,8s and 6,7+ 1s, to the AV2 of 24,5+ 8,3s and 18,5+ 12s and to the 13,93 +1,7s and 12,1 +2,1s to before and after the intervention, respectively. Just  in the values of the AVMTT proposed a significant difference. The results of the control groups : to the AVMT2  of 13,1 + 3,2s and 13,9 + 5,8s , to the AVMT2 of 8,4 + 2,1s and 9+ 2,6s, to the AV2 of 31,6+ 16,3 s and 17,9+ 13,3s and to the AVT of 14,8 +7s and 10,9 +3,9s to after and before of the intervention, respectively. There were differences between in the values AV2 and AVT. The analyse of Correspondence from Spearman showed a significant change  in the demeanor just from the experimental group of the after and before the test. Conclusion : the tecnic of the biofeedback is able  to change and or developing the processes of the selective visual attention.
Keywords: .